Projetos pentecostais: organizações religiosas como empreendimentos e pastores como empreendedores - Pelais, Luiz Gustavo Beijo (2021)
The relationship between religion and economics is a classic issue for the Social Sciences, however it has been relegated to the background in recent times, whether by adherents of the idea that religions have a secondary importance in the social fabric, or by the irreversible separation of economics in relation to other social sciences. Inserting itself in this tradition of studies, this dissertation intends to contribute to the understanding of contemporary Pentecostalism as it is loaded with an ethics that is very much in line with the idea of the self made man. This ideology emerges as a response to recent changes in capitalism and in the labor market. A central subject of this process in Pentecostalism, in addition to all adherents, is the figure of the pastor, who, in our understanding, finds in the religious organization an opportunity to make a career, undertaking, "opening his own church", as recommended by the entrepreneurial “spirit”. Thus, for the development of the present work, a bibliographic research was carried out, reaching theoretical saturation in order to contemplate the background questions raised, as well as resorting to the use of secondary data for its corroboration. As a form of analysis, we critically frame the entrepreneurial ethos as a precarious response to an economicsocial condition that is also precariously emerging. Far from being a definitive reflection, we intend this to be the construction of a referential framework for future empirical analyses.